2023
DOI: 10.1145/3582688
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Survey of Few-shot Learning: Evolution, Applications, Challenges, and Opportunities

Abstract: Few-shot learning (FSL) has emerged as an effective learning method and shows great potential. Despite the recent creative works in tackling FSL tasks, learning valid information rapidly from just a few or even zero samples remains a serious challenge. In this context, we extensively investigated 200+ FSL papers published in top journals and conferences in the past three years, aiming to present a timely and comprehensive overview of the most recent advances in FSL with a fresh perspective, and to provide an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(58 citation statements)
references
References 159 publications
0
57
1
Order By: Relevance
“…Few-Shot Classification: Few-shot classification has re-ceived a lot of attention in recent years. While a variety of approaches [75] have been proposed, the most successful ones seek to transfer positive knowledge either by finetuning [1,12,79] or meta-learning [17,19,21,24,38,62,74,77,81]. Finetuning based few-shot learners can be viewed as specialists that perform well on the target domain [9,27,79], but suffer from catastrophic forgetting [70] on the base domain.…”
Section: Related Workmentioning
confidence: 99%
“…Few-Shot Classification: Few-shot classification has re-ceived a lot of attention in recent years. While a variety of approaches [75] have been proposed, the most successful ones seek to transfer positive knowledge either by finetuning [1,12,79] or meta-learning [17,19,21,24,38,62,74,77,81]. Finetuning based few-shot learners can be viewed as specialists that perform well on the target domain [9,27,79], but suffer from catastrophic forgetting [70] on the base domain.…”
Section: Related Workmentioning
confidence: 99%
“…The results of other methods within this category are even lower. When comparing the use of ResNet10 (90 25.25% of ChestX) as the backbone for [124] on BSCD-FSL, it is observed that while increasing the depth of the network enhances performance on near-domain datasets (CropDiseases, EuroSAT), it deteriorates performance on distant-domain datasets (ISIC, ChestX). As such, the best balance of near-domain and distant-domain performance is achieved when using ResNet10 as the backbone.…”
Section: Evaluation For Parameter-based Approachesmentioning
confidence: 99%
“…Therefore, the goal of FSL is to leverage prior knowledge to learn new tasks with only a few labeled samples, which has attracted significant attention due to its crucial industrial and academic applications. Since the introduction of this problem in 2006 [18], numerous research methods have been proposed [61,75,87,90,114].…”
Section: Introductionmentioning
confidence: 99%
“…FSL is an emerging paradigm that addresses these challenges by producing creative work on data, models, and algorithms. According to [8], FSL techniques can be divided into data augmentation, multimodal learning, meta-learning [9]- [11], and transfer learning (TL) [12]- [14]. One critical issue of FSL in wireless communications is that the data from different environments are heterogeneous and the samples of a new environment are small.…”
Section: Introductionmentioning
confidence: 99%